a) (3a+2b) (a-4b) =
b) (2x-3y) (3x-2y) =
c) (5a²-b (2b+3b) =
d) (m+2n) (5m-2n) =​



Odpowiedź :

A) 4a-2b

B)5x-5y

C)25a+4b

D)6m

(Nie jestem 100% pewna czy dobrze)

Odpowiedź:

A=3[tex]a^{2}[/tex]-12ab+2ab-8[tex]b^{2}[/tex]=3[tex]a^{2}[/tex]-10ab-8[tex]b^{2}[/tex]

B=6[tex]x^{2}[/tex]-4xy-9xy+6[tex]y^{2}[/tex]=6[tex]x^{2}[/tex]-13xy+6[tex]y^{2}[/tex]

C=10[tex]a^{2}[/tex]b+15[tex]a^{2} b^{2}[/tex]-2[tex]b^{2} -3b^{2}[/tex]=10[tex]a^{2} b+15a^{2}b^{2} -5b^{2}[/tex]

D=5[tex]m^{2} -2mn+10mn-4n^{2}[/tex]=[tex]5m^{2} +8mn-4n^{2}[/tex]